Odes of Solomon: a commentary - Lattke, Michael (Hermeneia--a critical and historical commentary on the Bible, 2009)
Early testimonies -- Manuscripts and quotations of the Odes of Solomon -- Authorship -- Date of composition -- Language of composition -- Area of origin -- The Odes of Solomon and their place in antique religion and literature -- Literary forms and devices in the Odes of Solomon -- Editions and translations of the Odes of Solomon up to 1909 -- Editions and translations of the Odes of Solomon since 1909 -- Ode 1 : the wreath of truth -- Ode 3 : metaphors of love and gnōsis -- Ode 4 : a prayer in the form of a dialogue containing various teachings -- Ode 5 : my hope, my deliverance -- Ode 6 : spirit and gnōsis of the Lord, myth of the river, parable of the water of life -- Ode 7 : the Lord and Father of gnōsis, Epiphany and salvation of the Son, gnōsis of the Lord -- Ode 8 : speech of the Redeemer, Revealer, and Mediator of creation -- Ode 9 : redemptive address -- Ode 10 : mythological address of the Redeemer and Revealer -- Ode 11 : a redeemed one witnesses in metaphorical speech -- Ode 12 : the truth, the Word, and the aeons -- Ode 13 : admonitory parable of the mirror -- Ode 14 : childlike trust in the Lord -- Ode 15 : address of the Redeemed One and Redeemer : the Lord as the sun -- Ode 16 : hymnic self-portrait and doctrine of creation -- Ode 17 : mythological address of the Redeemed Redeemer with a Christological doxology -- Ode 18 : the plērōma and the Gnostics -- Ode 19 : the milk of the Father and the mother of the Son -- Ode 20 : from righteousness to glory -- Ode 21 : address by the exalted, redeemed, and glorifying One -- Ode 22 : dualistic mythos with traditional eschatology -- Ode 23 : mythological and metaphorical account of the heavenly letter (with didactic introduction and invitation) -- Ode 24 : dove and Messiah, disaster and floods, depraved ones and Gnostics -- Ode 25 : a redeemed one speaks of being saved -- Ode 26 : ode on the odes of the Lord -- Ode 27 : the crucifixion interpreted as ascent into heaven -- Ode 28 : the spirit of life and my redemption -- Ode 29 : address of a redeemed believer in Christ (in part as a narrative) -- Ode 30 : the living spring of the Lord -- Ode 31 : the manifestation of the justified Lord and his redemptive function -- Ode 32 : joy, light, and word of the blessed--and truth itself -- Ode 33 : dualistic myths and the address of the perfect virgin "grace" -- Ode 34 : authentic and inauthentic (above and below) -- Ode 35 : address of one who has been redeemed -- Ode 36 : address of the exalted one -- Ode 37 : address of one who is redeemed (on the cross?) -- Ode 38 : the redeemed I and the address of truth personified -- Ode 39 : parable about the power of God and the Kyrios Christos -- Ode 40 : hope, hymns, and redemption -- Ode 41 : call to rejoice, first-person address by the Son, and Christological poem -- Ode 42 : mythological address of the exalted and redeemed Redeemer